Fracture, Fatigue, Failure, and Damage Evolution, Volume 5 Proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics - Carroll, Jay.; Carroll, Jay.; Daly, Samantha.; Daly, Samantha. (Conference Proceedings of the Society for Experimental Mechanics Series,, 2015)
Fracture, Fatigue, Failure and Damage Evolution, Volume 5: Proceedings of the 2014 Annual Conference on Experimental and Applied Mechanics, the fifth volume of eight from the Conference, brings together contributions to this important area of research and engineering.  The collection presents early findings and case studies on a wide range of areas, including: Mixed Mode Fracture I: Emphasis on Modeling Mixed Mode Fracture II: Emphasis on Experimental Measurements Full-Field Measurements of Fracture Microscale & Microstructural Effects on Mechanical Behavior I: Nanoscale Effects Microscale & Microstructural Effects on Mechanical Behavior II: MEMS Microscale & Microstructural Effects on Mechanical Behavior III: Microstructure Microscale & Microstructural Effects on Mechanical Behavior IV: Shape Memory Alloys Fracture & Fatigue of Composites   Fracture & Fatigue for Engineering Applications Wave-Based Techniques in Fracture & Fatigue I Wave-Based Techniques in Fracture & Fatigue II: Acoustic Emissions.